Pengaruh Penggunaan Media Pembelajaran Video Interaktif Terhadap Hasil Belajar IPA Siswa Kelas VIII SMP Negeri 3 Kabupaten Sorong - Fanataf, Maria Fiane; Prabawati, Ratna; Ulfa, Nurul Alia (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
The purpose of this study was to determine the effect of the use of interactive video learning media on the science learning outcomes of Class VIII SMP Negeri 3 Sorong Regency. The type of research used in quantitative research with the research method used is a quasi-experimental method or quasi-experimental. While the research design used is a pretest-posttest design. The data collection techniques used in this study consisted of a pretest and a posttest. Data analysis was performed using statistical tests with SPSS version 26. The results of the study showed that the increase in students' science learning outcomes was marked by an increase in the number of students who initially did not get a good category score at the time of the pretest then increased to 16 students at the time of the posttest with a percentage of 61.54%. At the time of the pretest, there were no students who got a sufficient category score, while the value in the posttest was 10 students who got a sufficient category score with a percentage of 38.46%. In the pretest with the less category there were 26 students who got a percentage score of 100%, and in the posttest there were no students who got less. So it can be concluded that there is an increase in science learning outcomes of Class VIII SMP Negeri 3 Sorong Regency with the use of interactive video learning media.